2020
DOI: 10.3389/fphar.2020.607796
|View full text |Cite
|
Sign up to set email alerts
|

Acacetin Protects Against High Glucose-Induced Endothelial Cells Injury by Preserving Mitochondrial Function via Activating Sirt1/Sirt3/AMPK Signals

Abstract: The strategy of decreasing atherosclerotic cardiovascular disorder is imperative for reducing premature death and improving quality of life in patients with diabetes mellitus. The aim of this study was to investigate whether the natural flavone acacetin could protect against endothelial injury induced by high glucose and attenuate diabetes-accelerated atherosclerosis in streptozotocin-(STZ) induced diabetic ApoE−/− mice model. It was found that in human umbilical vein endothelial cells (HUVECs) cultured with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 53 publications
2
25
1
Order By: Relevance
“…It is one of the most important roles in vascular biology and atherogenesis [36]. For instance, SIRT1 can also protect endothelial cells from high glucose induced injury [34]. In the current study, we found SIRT1 is the target gene of LYPLAL1-DT, therefore elevates autophagy levels, thus decreasing apoptosis, in ammation, and monocyte adhesion of ECs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is one of the most important roles in vascular biology and atherogenesis [36]. For instance, SIRT1 can also protect endothelial cells from high glucose induced injury [34]. In the current study, we found SIRT1 is the target gene of LYPLAL1-DT, therefore elevates autophagy levels, thus decreasing apoptosis, in ammation, and monocyte adhesion of ECs.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, novel lncRNA LYPLAL1-DT was found to regulate the target gene SIRT1 by acting as a ceRNA of miR-204-5p. SIRT1 is an anti-autophagy factor that can reduce cell death [34], as well as regulate the apoptosis of endothelial cells through the mTOR pathway [35]. It is one of the most important roles in vascular biology and atherogenesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that HG can induce endothelial cell apoptosis and dysfunction by activating NF-B signaling, leading to diabetic vascular complications [ 40 ]. Han et al reported that HG can suppress cell viability, induce cell apoptosis and cause oxidative stress injury in HUVECs, resulting in a vascular disorder in patients with diabetes [ 41 ]. In the present study, our results indicated that HG can inhibit HUVECs viability and proliferation, inducing cellular dysfunction and limiting migration, angiogenesis and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a very recent report described the protective effect of the flavone acacetin against cardiac senescence via SIRT1-mediated activation of SIRT6/AMPK signalling pathway [ 51 ]. Likewise, the protection of acacetin against vascular hyperglycemic injury was related to SIRT1-mediated activation of SIRT3/AMPK [ 52 ]. Moreover, SIRT6 and SIRT3 mutually regulate each other’s activity to protect the heart from developing diabetic cardiomyopathy [ 53 ].…”
Section: Discussionmentioning
confidence: 99%